2019 IEEE 58th Conference on Decision and Control (CDC) 2019
DOI: 10.1109/cdc40024.2019.9030073
|View full text |Cite
|
Sign up to set email alerts
|

Youla-Kucera adaptive feedback disturbance rejection in the presence of plant uncertainties

Abstract: The stability of an adaptive disturbance rejection scheme based on the Youla-Kucera parameterization is investigated, in case of an uncertain plant model is used in the synthesis of the central controller. It is shown that stability is guaranteed provided that two conditions are satisfied at the same time: the first one is linked to the internal model principle, and the second one depends on the closed-loop poles location. For some uncertainties, these constraints cannot be met simultaneously with the minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…∞ . Consequently a sufficient stability condition for the closed-loop is (24). Now at the frequencies ω j , equation ( 14) must be So(e −iω j ) H R (e −iω j )H S (e −iω j )e −iω j do e −do iω j Bo(e −iω j ) , by combining with (24), one obtains condition (23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…∞ . Consequently a sufficient stability condition for the closed-loop is (24). Now at the frequencies ω j , equation ( 14) must be So(e −iω j ) H R (e −iω j )H S (e −iω j )e −iω j do e −do iω j Bo(e −iω j ) , by combining with (24), one obtains condition (23).…”
Section: Discussionmentioning
confidence: 99%
“…80, 244, 400, 686, 828, 1110, and 1200 Hz. The inequality (24) suggests to design So(z −1 ) H R (z −1 ) as series of band-pass filters with a strong amplification at these frequencies. Additionally, H R incorporates zeros at −1 and +1, in order to open the loop at 0 Hz and 0.5/T s Hz.…”
Section: Test-bench Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this solution needs to satisfy stability conditions which cannot be fulfilled for all systems especially when the uncertainty is large. A recent work Vau and Landau (2019) showed that this difficulty can be overcome by increasing the order of the filter Q. This solution is called YK overparametrization.…”
Section: Discussionmentioning
confidence: 99%